Fever in children: palpation, the understanding of mother and further Ã¢â¬Â¢ action - Purwoko, Purwoko (Universitas Gadjah Mada, 2003)
Background: Fever is the most common event lead the mother to bring her children to seek for health service. Assessment of fever by palpation is commonly done to recognize fever in children. Objective: The aim of this study was to examine the sensitivity of palpation and understanding of fever in children by mothers.Methods: This study was descriptive analytic design, done to mothers visited outpatient clinic Department of Child Health Dr. Sardjito Hospital from Januari until April 2001. Sample for study determined by systematic random sampling. Data were obtained by interview with the mothers using questionnaires and temperature measurements to children using thermometer. Data were analysed using Chi-square (c2), and logistic regression.Results: Most of (91%) all mothers (511) assessed fever in children by palpation and 23,1% used thermometer. Palpation by mothers had showed that 84.6% of mothers palpated fever rightly and 77.2% of mothers palpated non fever rightly. Most of (95.7%) mothers felt worried when their children got fever, with the reasons afraid of seizure (26.2%), or when they suffered from severe illness (64.0%). Mothers who understood about the definition of fever (> 37.50C) were more worried (OR: 3.80 (95% CI: 1.36-10.61%1 than they didnt. The first practice to manage fever in the family was giving antipyretic (72.0%). Antipyretics administration was based on consideration of antipyretic benefit (OR: 2.31 (95% CI: 1.51-3.54%)), and the availability of antipyretic in household (OR: 2.14 (95% CI: 1.423.23%1, but wasnt on mothers worrying (OR: .394 (95% CI: .12-1.35)).Conclusions: Palpation assess fever by mothers.The higher the understanding of mothers on fever the sooner they seek for help. Mothers understanding on the benefit of antipyretics and the availability of antipyretics at home make the mothers giving antipyretics sooner.Key words: fever-accuracy of fever-mothers knowledge-mothers attitude-antypyretics administration